Toleransi Antar Umat Beragama Perspektif Maftuh Basyuni - Muhayyan Ifkar; Mawardi Mawardi (Universitas Islam Tribakti Lirboyo Kediri, 2022)
This study aims to describe and analyze Maftuh Basyuni's thoughts on the concept of tolerance between religious communities. In addition, it represents the supporting and inhibiting factors of religious tolerance, according to Maftuh Basyuni. This research is library research (Library Research). The author performs steps of identification, collection, processing and assessment of existing data related to Interfaith Tolerance according to Maftuh Basyuni, both in the form of primary and secondary data. The results from this study: the concept of religious tolerance, according to Maftuh Basyuni, is dynamic because it is maintained from time to time which means attitudes and actions that do not allow the urge to differentiate between other groups, which then form an attitude of respect and respect for equality. Factors that support religious tolerance, according to Maftuh Basyuni, include cooperation among internal religious communities, between religious communities and between religious communities and the government. Meanwhile, the factors that hinder religious tolerance are some areas. It tends to be sensitive, related to houses of worship, easily provoked by shallow fanaticism, the emergence of sects and deviant teachings, and a lack of understanding of religious teachings and government regulations regarding spiritual life.